Experience with an electronic health record for a homeless population. - Blewett, D. R. (American Medical Informatics Association, 1999)
A computerized electronic medical record (EMR) system using client-server architecture was designed and implemented by the Laboratory of Computer Science for use by the Boston Health Care for the Homeless Program (BHCHP) to meet the unique medical record needs of the homeless. For the past three years, this EMR has been used to assist providers in the delivery of health care to the homeless population of Boston. As the BHCHP has grown and technology improved, it is important to review what features of the EMR work, and to investigate what improvements can be made for the better delivery of care to the homeless, especially as we approach the next century.